Overview of Possible Relationship Management Aspects for the Governance of CCU/S - Kádár, Krisztina (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2025)
Purpose – This study explores the role of relationship management in supporting the governance of Carbon Capture, Utilization, and Storage (CCU/S) technologies, which are considered vital for achieving climate goals. Despite their potential, CCU/S technologies are emerging technologies, currently at a quite low technology readiness level that face governance challenges due to technical, financial, and socio-political uncertainties. This paper addresses a research gap by investigating how relationship management can foster collaboration, reduce stakeholder risks, and facilitate coordinated implementation.Design/methodology/approach – The study adopts an interdisciplinary literature review as its methodological approach, synthesizing approaches to relationship management that extend beyond the corporate context, offering insights relevant to CCU/S governance. The review examines key relationship management strategies, including government relations, public relations, corporate social responsibility, public-private partnerships, partner relationship management and citizen relationship management systems.Findings – The findings reveal that successful CCU/S governance depends on fostering long-term, trust-based cooperation between public and private actors. Relationship management strategies that emphasize transparency, inclusive communication, and adaptive stakeholder coordination are especially relevant. Real-world practices, such as Norway’s Longship project, illustrate the practical applicability of these concepts.Originality – This paper is among the first to analyze relationship management through the lens of CCU/S governance, offering a conceptual foundation for future empirical research. It highlights the importance of integrating socio-political dynamics into technology governance and provides aspects to support the deployment of CCU/S technologies at the national level.